2017
DOI: 10.5539/elt.v10n5p139
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative and Self-directed Learning Strategies to Promote Fluent EFL Speakers

Abstract: Speaking English with fluency is one of the most demanding challenges students and teachers face in many educational communities, and it has been claimed that fluency problems can derive from lack of practice during independent study. This research article reports on a mixed-methods study that analyzed the effects of using collaborative and self-directed learning strategies through speaking tasks aimed at developing oral fluency. This study was carried out with a group of 10 students with a pre-intermediate le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 23 publications
2
23
0
1
Order By: Relevance
“…Here, the collaborative role of the language teacher and the peers are of primary importance as a motivating factor. In line with this point, Buitrago (2017) investigated the effects of SDL and within-class collaborative learning on enhancing the speaking skills of undergraduate EFL students at a Colombian university. She found that when students engaged in SDL and then shared what they have learned with each other in the class, their oral communication skills improved, their language anxiety decreased, and their self-confidence enhanced.…”
Section: Technology-enhanced Sdl In Efl Educationmentioning
confidence: 99%
“…Here, the collaborative role of the language teacher and the peers are of primary importance as a motivating factor. In line with this point, Buitrago (2017) investigated the effects of SDL and within-class collaborative learning on enhancing the speaking skills of undergraduate EFL students at a Colombian university. She found that when students engaged in SDL and then shared what they have learned with each other in the class, their oral communication skills improved, their language anxiety decreased, and their self-confidence enhanced.…”
Section: Technology-enhanced Sdl In Efl Educationmentioning
confidence: 99%
“…Temerová (2007) pointed out that speaking a foreign language is a necessity for everyone in general and students in particular. Therefore, Buitrago (2017) asserted that the development of speaking skills should be a priority.…”
Section: Literature Review and Related Studiesmentioning
confidence: 99%
“…Thus, fluency can be acquired when interacting with others collaborative and by making mistakes. Learning collaboratively motivate students to speak fluently, engage them in realistic communicative situations, increase their confidence, and make their personal reflection (Buitrago, 2017).…”
Section: Literature Review and Related Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Peserta didik diharapkan bisa bekerja dalam kelompok untuk menunjukkan tujuan dalam meningkatkan kemampuan mereka dalam bekerja sama dengan yang lainnya. Pendapat yang sama dikemukakan oleh Vigotsky, perspektif konstruktivis (Buitrago, 2017) mengungkapkan bahwa pembelajaran kolaborasi adalah sebuah pendekatan yang sangat kuat yang dilakukan oleh perorangan bersama-sama untuk membangun pengetahuan dan mencapai tujuan bersama. Bekerjasama dalam sebuah kelompok dengan mempertahankan konsep tentunya akan memiliki pencapaian yang lebih baik daripada bekerja sendiri.…”
Section: Pendahuluanunclassified